APPLICATION OF NORMAL PARAMETER REDUCTION OF SOFT SETS IN DECISION MAKING - J.D.Thenge; B.S.Reddy (International Journal of Innovations in Engineering Research and Technology, 2021)
In this paper we discuss normal parameter reduction of Soft sets and weapply the normalparameter reduction algorithm to decision making problem ofchoosing a better smart phone which are available in Indian market.